(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
The ethanolic extract of Dactyloctenium aegyptium was investigated for its anti-ulcer activity against aspirin plus pylorus ligation induced gastric ulcer in rats, HCl -Ethanol induced ulcer in mice and water immersion stress induced ulcer in rats at 300 mg/kg body weight. p. o. A significant (P<0.01, P<0.001) anti-ulcer activity was observed in all the models. Pylorus ligation showed significant (P<0.01) reduction in gastric volume, free acidity and ulcer index as compared to control. It also showed 89.71% ulcer inhibition in HCl- Ethanol induced ulcer and 95.3% ulcer protection index in stress induced ulcer. This present study indicates that Dactyloctenium aegyptium extract has potential anti ulcer activity in the three models tested.